2015
DOI: 10.1136/bmjopen-2014-006474
|View full text |Cite
|
Sign up to set email alerts
|

Can probiotic yogurt prevent diarrhoea in children on antibiotics? A double-blind, randomised, placebo-controlled study

Abstract: ObjectiveTo estimate the efficacy of a probiotic yogurt compared to a pasteurised yogurt for the prevention of antibiotic-associated diarrhoea in children.Design and settingThis was a multisite, randomised, double-blind, placebo-controlled clinical trial conducted between September 2009 and 2012. The study was conducted through general practices and pharmacies in Launceston, Tasmania, Australia.Participants and interventionsChildren (aged 1–12 years) prescribed antibiotics, were randomised to receive 200 g/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 27 publications
2
61
0
4
Order By: Relevance
“…Furthermore, our yogurt contained LF and also lactic bacteria. Habitual yogurt consumption and food intake, including lactic bacteria, have been reported to alleviate gastrointestinal symptoms [30][31][32][33][34][35]. Yogurt containing lactic bacteria without LF might affect intestinal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our yogurt contained LF and also lactic bacteria. Habitual yogurt consumption and food intake, including lactic bacteria, have been reported to alleviate gastrointestinal symptoms [30][31][32][33][34][35]. Yogurt containing lactic bacteria without LF might affect intestinal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…There was also only one episode of minor diarrhoea (stool consistency ≥5, ≥2 stools/day for ≥2 days in the probiotic group compared to 21 in the placebo group (Fisher’s exact p < 0.001). The probiotic group reported fewer adverse events (one had abdominal pain, one vomited and one had headache) than the placebo group (six had abdominal pain, four had loss of appetite and one had nausea).[89] Lactobacillus acidophilus La-5 Lactobacillus rhamnosus GG (LGG)Not specifiedStatistically significant differences were observed between both study and control groups regarding to frequency, degree of severity and duration of antibiotic associated diarrhea (AAD).[90] Lactobacillus acidophilus LA-5, Bifidobacterium lactis Bb12, and L. rhamnosus (LGG).Consumption of probiotic milk in pregnancy was associated with a slightly reduced risk of atopic eczema at 6 months and of rhinoconjuctivitis between 18 and 36 months, compared with no consumption during pregnancy. Maternal history of allergic disease did not notably influence the associations.…”
Section: Probiotic Lab and Yoghurt Starter Culturesmentioning
confidence: 99%
“…Among these probiotic strains, B. lactis Bb12 and L. rhamnosus GG are the most studied and their health-promoting properties are well documented (Mohan et al, 2006;Roselli et al, 2006;Wang et al, 2004). In instance, a yogurt combination of L. rhamnosus GG, L. acidophilus La-5 and B. lactis Bb12 was shown to be an effective method for reducing the incidence of antibiotic-associated diarrhea in children (Fox et al, 2015). Probiotic species (B. lactis Bb12 and L. rhamnosus GG) used in this study possess a number of identified physiological health benefits, thus we assume that these bacteria could contribute jointly to re-establish and maintain a stable microbiota composition in mice.…”
Section: Discussionmentioning
confidence: 99%